The Architecture of Space-Time in the Novels of Jane Austen - Baublyté Kaufmann, Ruta (Springer International Publishing, 2018)
This book argues that there are recurrent spatiotemporal patterns and structures in six Jane Austen novels which constitute a source of enduring, if unconscious, pleasure. More precisely, the book contends that there are overlapping natural and cultural cycles which co-exist in a constantly transmuting space-time and which are counterpointed with the linearity of pivotal events that drive the plot forwards. This work examines the psychological relations to these space-time patterns of the characters, principally the heroines, focusing on the transformations of their emotional states which prompt linear leaps.